EXPERIENCE OF THE USE OF VARIOUS METHODS OF SURGICAL TREATMENT OF THE CHEILOSCHISIS AND PALATE - M.M. ISMOILOV; N.D. MUKHIDDINOV; M.S. SAIDOV (Avicenna Tajik State Medical University, 2017)
Objective: To study the results of surgical treatment of patients with cheiloschisis and palate. Methods: 230 patients with cheiloschisis and palate were examined in the period from 2009 to 2016. Patients with a congenital cleft of the upper lip were 55; patients with isolated cleft palate 152; and other patients have combined defects. Results: A total of 287 surgical interventions were performed. It was established that the use of Millard's operation in the congenital cleft of the upper lip is preferable to the Tennesy operation, despite the great difficulties in performing the first. When the defects of the soft palate were eliminated, the technique of using the posterior-pharyngeal flaps was most effective. Conclusion: The choice of the method of surgical treatment of cheiloschisis and palate should be strictly individual, which ultimately contributes to a significant decrease of frequency of postoperative complications.